Palmitylation of an amino-terminal cysteine motif of protein tyrosine kinases p56lck and p59fyn mediates interaction with glycosyl-phosphatidylinositol-anchored proteins. - Shenoy-Scaria, A M (1993)
Cross-linking of glycosyl-phosphatidylinositol (GPI)-anchored membrane proteins on T cells can trigger cell activation. We and others have shown an association between GPI-anchored proteins and the protein tyrosine kinases (PTKs) p56lck and p59fyn, suggesting a pathway for signaling through GPI-anchored proteins. Studies of decay-accelerating factor (DAF) or CD59 in either the C32 cell line or the HeLa cell line transfected with PTK cDNA demonstrated that the GPI-anchored proteins associated noncovalently with p56lck and p59fyn but not with p60src. Nonmyristylated versions of p56lck and p59fyn also failed to associate with the GPI-anchored proteins. Mutational analysis of the PTK demonstrated that the association with the GPI-anchored proteins mapped to the unique amino-terminal domains of the PTK. A chimeric PTK consisting of the 10 amino-terminal residues of p56lck or p59fyn replacing the corresponding amino acids in p60src was sufficient for association with DAF, but the converse constructs containing the first 10 amino acids of p60src plus the remainder of p56lck or p59fyn did not associate with DAF. Mutation of cysteine to serine at positions 3 and 6 in p59fyn or positions 3 and 5 in p56lck abolished the association of these kinases with DAF. Mutation of serine to cysteine at positions 3 and 6 in p60src conferred on p60src the ability to associate with DAF. Direct labeling with [3H]palmitate demonstrated palmitylation of this amino-terminal cysteine motif in p56lck. Thus, palmitylation of the amino-terminal cysteine residue(s) together with myristylation of the amino-terminal glycine residue defines important motifs for the association of PTKs with GPI-anchored proteins.